DEVELOPMENT OF REHABILITATION ORIENTED RUSSIAN INSTITUTION OF BANKRUPTCY - Vаleriy Nikolaevich Alferov (Модернизация, инновация, развитие, 2016)
The paper conducted a study on the mechanisms of the development of Russian rehabilitative orientation of the institution of bankruptcy. Objectivs. To analyze the existing conditions and particularly the implementation of the institution of bankruptcy of legal entities in Russia and abroad and on the basis of foreign experience to consider proposals for the development of its rehabilitation orientation.Methods. Empirical and economic and statistical research methods based on the Russian and international practice, implementation of bankruptcy legislation. Results. A generalization of the features of the implementation of domestic and foreign institution of bankruptcy and considered proposals for the development of its rehabilitation orientation. Conclusions and Relevance. In the Russian legislation on bankruptcy is necessary to develop rehabilitation procedure of bankruptcy to achieve the goal of a public law character – the restoration of the debtor's solvency. At present, primary importance should be given to the development of pre-trial financial recovery of debtors, including through the conciliation.